2020
DOI: 10.47197/retos.v0i39.79755
|View full text |Cite
|
Sign up to set email alerts
|

Middle school students’ views about physical education: A comparative study between four European countries (Opiniones de los estudiantes de secundaria sobre la educación física: Un estudio comparado entre cuatro países europeos)

Abstract: Abstract. Comparable and cross-national research is needed to examine students’ views on the role of physical education (PE) in promoting active and healthy lifestyles, particularly in non-English speaking contexts. Thus, the present study aims to investigate and compare the views of middle school students from four European countries towards PE, considering cross-national and gender variables. In this cross-sectional study, 1244 middle school students (635 boys, 609 girls; Mean age = 14.3±0.9 years) from a pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The undergraduate students of CLSU and CAPSU have a keen interest in physical education and actively participate in various school activities. Prior research has indicated that male students exhibit a greater inclination toward physical education, place a higher level of importance on its content, and possess a more favorable attitude toward the subject in comparison to their female counterparts (Sofi et al 2019, Perić et al 2020. Moreover, in accordance with additional scholarly investigations, it has been shown that female students have a greater grasp of conceptual knowledge in the field of physical education when compared to their male counterparts (Thomas & Ti 2021).…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…The undergraduate students of CLSU and CAPSU have a keen interest in physical education and actively participate in various school activities. Prior research has indicated that male students exhibit a greater inclination toward physical education, place a higher level of importance on its content, and possess a more favorable attitude toward the subject in comparison to their female counterparts (Sofi et al 2019, Perić et al 2020. Moreover, in accordance with additional scholarly investigations, it has been shown that female students have a greater grasp of conceptual knowledge in the field of physical education when compared to their male counterparts (Thomas & Ti 2021).…”
Section: Methodsmentioning
confidence: 87%
“…Furthermore, the presence of sex-based barriers and disparities has been widely observed in several contexts, ranging from the integration of physical activities and organized sports to the cultivation of students' engagement in physical education. Multiple research studies have indicated that male students exhibit higher levels of enthusiasm toward physical education in comparison to their female counterparts (Sofi et al 2019, Perić et al 2020. According to empirical research, it has been observed that male students exhibit a higher tendency to engage in team sports, such as basketball, whilst female students demonstrate a greater inclination toward individual sports, such as dancing and exercising (Cowley et al 2021, Cruz 2022, Ricardo et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, issues of inequalities regarding sex have been predominantly evident worldwide, especially when dealing with the interest of students in Physical Education activities being introduced to them (e.g., physical activities and sports events). Grounded on the findings of various scholars, higher interest and positive perception scores toward Physical Education are predominantly evident for males compared to their counterparts (Perić et al, 2020;Sofi, Waseem and Padder, 2019). Additionally, findings exposed that male students are highly more interested and engaged in organized contact sports (e.g., basketball), while female students are more on into individual sports, dancing, and exercise (Cowley et al, 2021;Cruz, 2022;Deaner, Balish and Lombardo, 2016;Pituk and Cagas, 2019;Ricardo et al, 2022).…”
Section: Individual Interest In Physical Education and School Engagementmentioning
confidence: 97%
“…Respondents are free to withdraw or to ask for debriefing anytime. give more importance to the content, and have a more positive attitude towards the subject compared to females (Perić et al, 2020;Sofi et al, 2019). Contrastingly, based on other published scholarly papers, it was found that conceptual knowledge in Physical Education is higher for female students compared to males (Thomas and Ti, 2021).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…These findings run counter to a number of scholarly publications in which the scholars emphasize the different ways in which students' interests are piqued when gender is being talked about. Research found that male students are more enthusiastic about PE, place more value on the subject matter, and view it in a positive light than female students [66,67]. To the contrary, previous research in the academic literature reveals that female students have a deeper conceptual understanding of physical education than male students [68].…”
Section: Significant Variance In Individual Interest and School Engag...mentioning
confidence: 99%